Pteridophytic Flora of Mehao Wildlife Sanctuary, Lower Dibang Valley, Arunachal Pradesh (Eastern Himalaya) - Rawat, Vineet Kumar (Indian Forester, 2012)
Over 500 specimens of pteridophytes (Ferns and fern allies) were collected from Mehao Wildlife Sanctuary, Lower Dibang Valley District of Arunachal Pradesh during exploration tours. The identification of specimens revealed the occurrence of 205 species of pteridophytes under 75 genera and 37 families from ten localities of the study area, of these 20 species belongs to Fern allies and the rest 185 to the Ferns including 6 sub species. The flora is diverse and rich with rare (51 species), endemic (7 species) and curious pteridophytic species. Nine species viz. Oleandra musifolia, Metteucia orientalis, Plagiogyria glaucascens, Arthromeris lehmanni, A. wardii, Hupergia dixitiana and Leucostegia immerse, Elaphoglossum marginatum, Idiogramma microphylla are recorded for the first time from Arunachal Pradesh. It is observed that the terrestrial species constitute more than 62% while epiphytes as approximately 23% of the total pteridophytic flora. Only 14% species have been found as lithophytes in the sanctuary. The present study shows that family Polypodiaceae is the largest family and represented by 33 species, which is followed by Athyreaceae (24 species), Dryopteridaceae (19 species), Thelypteridaceae (18 species) and Aspleniaceae (11 species).